HYDRAULIC OPERATED STATOR STAMPING MACHINE - Mr.Aumsai R .Waghmare; Mr.Shubham S. Shete (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Stator stamping hydraulic machine is different from the conventional stamping machine, in which the system is quicker and gives highest productivity. Stator have the number of slot on outside perimeter. And number of teeth on inside perimeter. Winding is fitted in the teeth. And the winding which fill inside the stator called as field winding, where the winding field inside the rotor called as armature winding. These stamping has to come in exact and accurate position. If they are not in accurate position then the winding can't fill inside the stator as well as rotor also. The slot are use to make the exact position of those stamping. Hydraulic operated stator stamping machine is use to make the stator stamping combination with exact and accurate position. This machine use hydraulic system to make it possible. Hydraulic system use in this machine is conventional hydraulic system. This hydraulic system use number of cylinder to complete the operation. The stator stamping combination is generated in single working stroke. The stator is produced by punching and stamped with stamp punching mode .This system gives accurately placed winding position by holding stator in properly design clamps. The system working done with the help of hydraulic actuators and high pressure hydraulic oil. The stamping starts by placing number of stator over a mandrel. The hydraulic operated stator stamping machine gives more stator stamping in single stroke of operation. Conventional method uses hydraulic presses and manual invention, which results in more noise and time consuming operation. and it reduces production rate because in single stroke of operation it cannot completed the whole stator stamping combination .So for this hydraulic operated special purpose stator stamping machine is more beneficial and higher productive.